Associations between IL-1[alpha], IL-1[beta], TNF[alpha], and IL-6 variations, and susceptibility to transposition of the great arteries - Atasoy Karakas, Latife; Tugrul, Duygu; Sahin Uysal, Nihal; Esin, Sertac; Tokel, Niyazi Kursat; Terzi, Yunus Kasim (BMC cardiovascular disorders, 2022)
Background To evaluate the relationship between IL-1[alpha] -889C/T (rs1800587), IL-1[beta] -511C > T (rs16944), TNF[alpha] -308G > A (rs1800629), TNF[alpha] -238G > A (rs361525), IL-6 -174G > C (rs1800795), and IL-6 -572G > C (rs1800796) polymorphisms and the susceptibility to transposition of the great arteries (TGA). Methods A prospective analysis was performed on mothers whose newborns were diagnosed as having TGA. For each case of TGA, a mother who gave birth to a healthy neonate in the same period was randomly selected for the control group. The sample size was calculated before planning the study with 80% power and 5% alpha. Results Twenty-seven mothers whose newborn had TGA anomalies (group 1) and 27 mothers whose newborn had no TGA (group 2) were included in the study. There were no significant differences between the groups in terms of maternal age, pregestational body mass index, gestational age at birth and infant sex (p > 0.05). The genotype and allele distributions of IL-1[alpha] -889C/T (rs1800587), IL-1[beta] -511C > T (rs16944), TNF[alpha] -308G > A (rs1800629), TNF[alpha] -238G > A (rs361525), IL-6 -174G > C (rs1800795) and IL-6 -572G > C (rs1800796) gene variants were not different between the two groups (p > 0.05). Conclusions There was no relation between IL-1[alpha], IL-1[beta], IL-6, and TNF[alpha] promoter gene polymorphisms and TGA occurrence in our study group. Trial registration: This present prospective case-control study was conducted in Baskent University Hospital, Ankara, Turkey, between May 2020 and November 2021. Ethical approval was obtained from the university's Clinical Research Ethics Commitee (No: KA20/211) in accordance with the Declaration of Helsinki. Keywords: IL-1[alpha] -889C/T (rs1800587), IL-1[beta] -511C > T (rs16944), TNF[alpha] -308G > A (rs1800629), TNF[alpha] -238G > A (rs361525), IL-6 -174G > C (rs1800795), IL-6 -572G > C (rs1800796), Promoter, Polymorphisms, Transposition of the great arteries